THE EFFECT OF QUALITY OF SERVICE - Meidina, Angennisa Prima; Brahmantyo, Himawan; Mariati, Sri (Jurnal Penelitian Pariwisata, 2022)
This study aims to analyze the effect of service quality and facilities on tourist satisfaction at Jatimalang Beach. This type of research uses a descriptive quantitative survey method. The data was processed by multiple regression analysis with the help of the SPSS program. The population of this research is tourists who have visited Jatimalang Beach with a sample of 100 respondents, sampling using an accidental sampling technique. The results showed that the quality of services and facilities partially had a positive and significant effect on tourist satisfaction. The service quality of a tourist attraction is considered good and satisfying if it can provide services that exceed tourist expectations; if the service provided is lower than tourist expectations, then the service quality is considered poor. Facilities to meet the travel needs of tourists appear as a whole that is interconnected and complement each other so that in a tour, all the components used cannot be separated. Jatimalang Beach, Purworejo tourism managers are expected to pay attention to tourist loyalty, for example, by providing criticism and suggestions for tourist objects so that they can quickly evaluate what tourists want. Keywords: Service Quality, Facilities, Tourist Satisfaction